Diagnostico de la política educativa “Juntos leemos” para su implementación en la unidad educativa del milenio Guano - Samaniego Llerena, Shirley Fernanda (2024)
The objective of this research work was to develop a Diagnosis of the Educational Policy “Together We Read” for its implementation in the Guano Millennium Educational Unit, and thus be able to contribute to the strengthening of school education in the identified population. The work was developed through a mixed approach methodology; with a descriptive level, of basic modality; with the application of techniques and instruments such as interviews and surveys to collect information, to the selected population that included authorities, teachers and students from the educational unit. Thus, the main results indicated that there is knowledge of the educational policy but not its application and strengthening one hundred percent. Furthermore, there are no development activities for reading and writing and where students express their predisposition to learning. Therefore, a proposal focused on ten weeks of work is presented, presenting different activities, their methodology and evaluation to be implemented in the institution. Therefore, it is concluded that the reading conditions and the policy together we read is a very useful tool if it can be channeled and worked on in the school units. Thus, it is recommended to use the proposed guide and improve it as it is implemented according to the results obtained.